Rekonstrukcní výkony po exenteraci pánve - Cibula, D; Babjuk, M; Freitag, P; Fischerová, D; Pesková, M; Gürlich, R; Zivný, J (Ceska gynekologie, 2005)
OBJECTIVE: Review of reconstruction procedures following pelvic exenterations. DESIGN: Review article. SETTING: Department of Obstetrics and Gynecology, Department of Urology, 1st Department of Surgery, Faculty Teaching Hospital and 1st Medical Faculty of the Charles University, Prague. METHODS: Review and critical assessment of published data. CONCLUSIONS: Reconstruction procedures are important part of pelvic exenterations. The procedures are crucial for following quality of life. Currently the most frequently used techniques for isolated pelvic floor support are omental flaps (carpets), for combined reconstruction of pelvic floor and vagina TRAM (transverse rectus abdominis musculocutaneus flap). Reconstructions prolong operation time; however they are accompanied with low morbidity and some techniques decrease total morbidity of exenterative procedure. Total and posterior exenterations require sigmoideostomy in vast majority of cases. Low rectal anastomosis might be used in cases of supralevator procedures. They cause high morbidity especially in patients following radiotherapy. In these patients temporary diverting colostomy is being recommended. A bowel segment is usually used for urinary diversion following total or anterior exenteration. Golden standard remain the incontinent ureteroenterostomies using ileum or colon transversum. Currently continent diversions are considered more often due to encouraging results and good quality of life. Heterotopic diversions, with continent conduit and cutaneous stoma, are frequently used. Risk of serious complications, especially fistulas and stoma stenosis, after all types of diversions is possible to reduce by using appropriate bowel segment not handicapped by previous radiotherapy.
Keywords: Pelvic Exenteration; Urinary Diversion; pánev; exenterace pánve; zákroky plastické chirurgie; lidé; diverze moči; Colostomy; Plastic Surgery Procedures; Humans; kolostomie; Pelvis; ženské pohlaví; Female